Monitoring and support received by the self-evaluation commissions of the Division of Educology - García Vargas, Silvia (2024)
The permanent activity Self-Evaluation and Quality Management of the Division of Educology (APAGCDE), carries out within its multiple tasks; accompany and follow up on the improvement plans of the self-assessment and accreditation commissions (CAE's) of own and shared careers, therefore, hold meetings and consult with different social actors involved in the substantive actions of the Academic Unit (UA) , as are the representatives of the Division of Educology (DED) in the CAE's, this with the purpose of offering the support required from the UA Directorate and this permanent activity. In 2023, the APAGCDE followed up, held an annual meeting and applied a consultation to the people participating in said commissions, to know the current status of the self-assessment and accreditation processes of the DED careers, as well as assess the support that They receive these commissions from the curricular advisory service of the Vice-Rector for Teaching (VD). The consultation responds to a formative evaluation that promotes suitable and relevant actions that benefit the DED and university bodies with the sole purpose of continuing to improve actions and seek excellent academics.